Fibre Spectroscopy of Nanoscale Spontaneous Parametric Down-Conversion - Santiago Cruz, Tomás; Zhang Haizhong; Anthur, Aravind P.; Krivitsky, Leonid; Chekhova, Maria (2020 CONFERENCE ON LASERS AND ELECTRO-OPTICS PACIFIC RIM (CLEO-PR), 2020)
CRIS-Team WoS Importer:2021-06-11

Flat-optics generation of broadband photon pairs with tunable polarization entanglement - Sultanov, Vitaliy; Santiago Cruz, Tomás; Chekhova, Maria (Optics Letters, 2022)
The concept of “flat optics” is quickly conquering different fields of photonics, but its implementation in quantum optics is still in its infancy. In particular, polarization entanglement, strongly required in quantum photonics, is so far not realized on “flat” platforms. Meanwhile, relaxed phase matching of “flat” nonlinear optical sources enables enormous freedom in tailoring their polarization properties. Here we use this freedom to generate photon pairs with tunable polarization entanglement via spontaneous parametric downconversion (SPDC) in a 400-nm GaP film. By changing the pump polarization, we tune the polarization state of photon pairs from maximally entangled to almost disentangled, which is impossible in a single bulk SPDC source. Polarization entanglement, together with the broadband frequency spectrum, results in an ultranarrow (12 fs) Hong–Ou–Mandel effect and promises extensions to hyperentanglement.
CRIS-Team Scopus Importer:2022-08-12

Photon pairs bi-directionally emitted from a resonant metasurface - Son, Changjin; Sultanov, Vitaliy; Santiago Cruz, Tomás; Anthur, Aravind P. P.; Zhang, Haizhong; Paniagua-Dominguez, Ramon; Krivitsky, Leonid; Kuznetsov, Arseniy I. I.; Chekhova, Maria (Nanoscale, 2023)
Metasurfaces are artificially structured surfaces able to control the properties of light at subwavelength scales. While, initially, they have been proposed as means to control classical optical fields, they are now emerging as nanoscale sources of quantum light, in particular of entangled photons with versatile properties. Geometric resonances in metasurfaces have been recently used to engineer the frequency spectrum of entangled photons, but the emission directivity was so far less studied. Here, we generate photon pairs via spontaneous parametric down conversion from a metasurface supporting a quasi-bound state in the continuum (BIC) leading to remarkable emission directivities. The pair generation rate is enhanced 67 times compared to the case of an unpatterned film of the same thickness and material. At the wavelength of the quasi-BIC resonance, photons are mostly emitted backwards, while their partners, spectrally detuned by only 8 nm, are emitted forwards. This behavior demonstrates fine spectral splitting of entangled photons and their bi-directional emission, never before observed in nanoscale sources. We expect this work to be a starting point for the efficient demultiplexing of photons in nanoscale quantum optics.
CRIS-Team WoS Importer:2023-02-10

Resonant metasurfaces for generating complex quantum states - Santiago Cruz, Tomás; Gennaro, Sylvain D.; Mitrofanov, Oleg; Addamane, Sadhvikas; Reno, John; Brener, Igal; Chekhova, Maria (Science, 2022)
Quantum state engineering, the cornerstone of quantum photonic technologies, mainly relies on spontaneous parametric downconversion and four-wave mixing, where one or two pump photons spontaneously decay into a photon pair. Both of these nonlinear effects require momentum conservation for the participating photons, which strongly limits the versatility of the resulting quantum states. Nonlinear metasurfaces have subwavelength thickness and allow the relaxation of this constraint; when combined with resonances, they greatly expand the possibilities of quantum state engineering. Here, we generated entangled photons via spontaneous parametric downconversion in semiconductor metasurfaces with high-quality factor, quasi-bound state in the continuum resonances. By enhancing the quantum vacuum field, our metasurfaces boost the emission of nondegenerate entangled photons within multiple narrow resonance bands and over a wide spectral range. A single resonance or several resonances in the same sample, pumped at multiple wavelengths, can generate multifrequency quantum states, including cluster states. These features reveal metasurfaces as versatile sources of complex states for quantum information.
CRIS-Team Scopus Importer:2022-09-09

Spontaneous Parametric Down-Conversion in Nonlinear Metasurfaces - Fedotova, Anna; Santiago Cruz, Tomás; Sultanov, Vitaliy; Weissflog, Maximilian; Younesi, Mohammadreza; Staude, Isabelle; Pertsch, Thomas; Setzpfandt, Frank; Chekhova, Maria (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Resonant nonlinear metasurfaces gained a lot of interest in the past decade because of their unique features such as subwavelength thickness and ability to control spatial and temporal properties of light. They have proved to be efficient for classical processes such as second-harmonic generation (SHG), but their potential in quantum nanophotonics - for example for biphoton generation via spontaneous parametric down-conversion (SPDC) - remained mostly unexplored. Recently, SPDC at the nanoscale was established in nonlinear thin films [1] and implied in single nanoresonators [2], albeit with very low efficiency.
CRIS-Team Scopus Importer:2021-10-29